Antiferromagnetism and its origin in iron-based superconductors (Review Article) - Ding, Ming-Cui; Lin, Hai-Qing; Zhang, Yu-Zhong (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
In iron-based superconductors, unravelling the origin of the antiferromagnetism is a crucial step towards understanding the high-Tc superconductivity as it is widely believed that the magnetic fluctuations play important roles in the formation of the Cooper pairs. Therefore, in this paper, we will briefly review experimental results related to the antiferromagnetic state in iron-based superconductors and focus on a review of the theoretical investigations which show applicability of the itinerant scenario to the observed antiferromagnetism and corresponding phase transitions in various families of the iron-based superconductors. A proposal of coupling between frustrated and unfrustrated bands for understanding the reduced magnetic moment typically observed in iron pnictides is also reviewed. While all the above theoretical investigations do not rule out a possible existence of localized electrons in iron-based superconductors, these results strongly indicate a close relation between itinerant electrons and the magnetically ordered state and point out the importance of taking into account the orbital degrees of freedom.